Cookies enriched with coffee silverskin powder and coffee silverskin ultrasound extract to enhance fiber content and antioxidant properties - Cecilia Dauber; Melissa Romero; Clarita Chaparro; Camila Ureta; Clara Ferrari; Romina Lans; Lucía Frugoni; María V. Echeverry; Beatriz Sánchez Calvo; Andrés Trostchansky; Marcelo Miraballes; Adriana Gámbaro; et al. (Applied Food Research, 2024)
Coffee is one of the most significant beverages consumed worldwide. However, the substantial production and consumption of coffee has led to the generation of large amounts of by-products, such as coffee silverskin (CS).The first objective was to study the ultrasound-assisted extraction (UAE) conditions from CS according to a simple factorial design, in order to obtain natural extracts as a source of polyphenols and caffeine with high antioxidant activity. The second objective was to include CS powder (CSP) or ultrasound CS extract (UCSE) in the elaboration of cookies, in order to obtain an enriched food product with potential health benefits for consumers.CS was characterized in terms of moisture, protein, lipids, ash, total dietary fiber, total phenol content (TPC) and antioxidant activity. The UCSE was characterized in terms of extraction yield, TPC, caffeine content and antioxidant activity (ABTS and ORAC assays).The best UCSE used for cookie elaboration was obtained at 60 min and 180 W with the following values: 8.8 %wt; 36.8 mg GAE/g; 62.7 µmol caffeine/g; 491.1 µmol/g (ABTS assay); 1012.4 µmol/g (ORAC assay). Finally, the cookies were sensory and chemically characterized. In the cookies containing UCSE the sensory acceptability was not modified with respect to the control cookies and an increase in TPC and antioxidant activity was achieved. However, the incorporation of CSP lead to a decrease in the acceptability despite the fact that the cookies constitute a source of fiber. Results reinforce the use of green extraction technologies to obtain antioxidants compounds from natural sources.